Oncocytic Tumors of The Adrenal Gland - Capela, Andreia (2013)
The oncocytic tumors of the adrenal gland are rare. To date there’s only 147 cases published. The authors present a case of a 34 year-old man admitted to the hospital with lumbar pain and fever. At medical examination a mass was found in the left upper quadrant of the abdomen. The hormonal measurements of the adrenal gland were normal and the abdominal angio CT showed a left retroperitoneal lesion measuring 145 x 157 x 128 mm with extensive necrotic and hemorrhagic areas. The patient underwent a complete surgical resection of the lesion. The mass weighted 1495g and the histological exam revealed an oncocytic tumor of the adrenal gland with uncertain potential. Most of the oncocytic tumors are non functioning and must be considered in the differential diagnosis of adrenocortical tumors. The biologic behavior and the prognosis of these tumors are variable and still need a better definition. Due to the rarity of these tumors the authors made a revision on the published bibliography.